Políticas de imaturidade - Garcia, Harete Vianna Moreno [UNIFESP] (2014)
The Municipal Council for the Children's and Adolescents' Rights (in Portuguese, Conselho Municipal de Direitos da Criança e do Adolescente, CMDCA) is a public body composed equally of governmental and non-governmental organizations whose role is, deliberatively, elaborating policies for the assistance to children's and adolescents' rights, as well as monitoring, controlling and evaluating the developed programs and actions. The objective of this research – developed in the Professional Master’s Degree Program of Universidade Federal de São Paulo – was, based on the concepts of Institutional Analysis, to take the CMDCA of the city of São Vicente as an analyzer of what I have called " immaturity policies". The methodology took place by the mapping of the forces in process, using the recorded narratives written by me and reports to track, analyze and produce experiences, the micropolitics in the CMDCA. In a qualitative approach, Intervention Research was applied. From the immersion in the field (which I attended to while being a counselour and SUS worker) emerged in the investigation some policies that I called "immaturity policies", which did not exist at first. Possible research outcomes operate in a certain immaturity policy that works in a key of recognition, anesthesia, understanding the world and life as being already known, experienced, either in the work of the council, public notices, documents production or a council that thinks by dichotomies of values, individual vs. society, adult world vs. infantile world... Another immaturity policy relates to tutelage, discipline, docile bo.dies, producing and naturalizing the lack related to the model of maturity, related to what should be done morally; which is expressed both in the understanding of what is the direct work with children and adolescents and in the production of public policies. A third immaturity policy concerns to incompleteness, where the shape has not yet been formed, the innocence of the vital processes when they can state themselves, may be the becoming-child, the becoming-teen. Finally, a immaturity policy with a "flexible" logic, operating in a business way, within the apparatus of the state or municipality, kind of a surf that asks for certain impersonality, a more flowing game, a bet on the capitalistic lightness, small businessmen of themselves, no stock, no shape. Subtle rearrangements to various alliances. Within the law, but not always ethical. Hyper connectivity always open to new networks... In this investigation with the CMDCA, becoming-child and becoming-teen operate, it is about living up to what has no limits, what is open, larval, which may encourage authoritarian and reactivity but also may launch the new.